New-onset hyperglycaemia and prolonged systemic corticosteroids therapy in mild COVID-19 patients as major risk factors for invasive mucormycosis: a preliminary study - Satyendra Khichar; Subhashree Samantaray; Deepak Kumar; Veena Mobarsa; Vidhi Jain; Vidhu Sharma; Kapil Soni; Bikram Choudhary; Amit Goyal; Durga Meena; Srikanth Srinivasan; Naveen Dutt; et al. (Current Medical Mycology, 2021)
Background and Purpose: Rapid surge of invasive mucormycosis has surprised the Indian healthcare system amidst the coronavirus disease-19 (COVID-19) pandemic. Hence, there is an urgent need to find the risk factors for the sudden rise in cases of invasive mucormycosis among COVID-19 patients. This study aimed to find crucial risk factors for the sudden surge of invasive mucormycosis in India.Materials and Methods: This case-control study included 77 cases of COVID-19 associated mucormycosis (CAM) who matched the controls (45 controls) in terms of age , gender, and COVID-19 disease severity. The control group included subjects that matched controls without mucormycosis confirmed by reverse transcription-polymerase chain reaction at our tertiary care center during April-May 2021. Probable predisposing factors, such as duration of diabetes mellitus (DM), history of recent hospitalization, duration of hospital stay, mode of the received oxygen supplementation, and use of steroids, zinc, vitamin c, and any other specific drugs were collected and compared between the two groups. Moreover, the laboratory parameters, like glycated hemoglobin (HbA1c), highly sensitive C-reactive protein (hs-CRP),and erythrocyte sedimentation rate (ESR) were analyzed to find out the significant association with CAM.Results: DM (Odds ratio=7.7, 95% CI 3.30-18.12; P=<0.0001) and high glycatedhemoglobin level (HbA1c>7.5 gm %) (odds ratio=6.2, 95% CI 1.4-26.7; P=0.014) weresignificant risk factors for the development of invasive mucormycosis among the COVID-19 cases. A higher number of mild COVID-19 cases developed CAM, compared to the moderate to severe cases (59.7% vs 40.3%). Use of systemic corticosteroids (odd ratio=5 with 95% CI 1.5-16.9; P=0.007) was found to be a risk factor for invasive mucormycosis only in mild COVID-19 cases. Use of oxygen, zinc, and vitamin C supplementation, and proprietary medicine did not lead to a significant risk of invasive mucormycosis in cases, compared to controls. Cases with invasive mucormycosis had a higher level of inflammatory markers (hsCRP and ESR, P=<0.001 and 0.002,respectively), compared to the controls.Conclusion: Uncontrolled and new-onset DM and the use of systemic corticosteroids in mild cases were significantly associated with a higher risk of invasive mucormycosis in COVID-19 cases. There should be a strong recommendation against the use of systemic corticosteroids in mild COVID-19 cases.